If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(x + 4) = 14(x + -2) Reorder the terms: 12(4 + x) = 14(x + -2) (4 * 12 + x * 12) = 14(x + -2) (48 + 12x) = 14(x + -2) Reorder the terms: 48 + 12x = 14(-2 + x) 48 + 12x = (-2 * 14 + x * 14) 48 + 12x = (-28 + 14x) Solving 48 + 12x = -28 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 48 + 12x + -14x = -28 + 14x + -14x Combine like terms: 12x + -14x = -2x 48 + -2x = -28 + 14x + -14x Combine like terms: 14x + -14x = 0 48 + -2x = -28 + 0 48 + -2x = -28 Add '-48' to each side of the equation. 48 + -48 + -2x = -28 + -48 Combine like terms: 48 + -48 = 0 0 + -2x = -28 + -48 -2x = -28 + -48 Combine like terms: -28 + -48 = -76 -2x = -76 Divide each side by '-2'. x = 38 Simplifying x = 38
| 67+4x+15=90 | | X^2-Y^2-6X-4Y+4=0 | | -6a^6+4a^5-2a^4= | | -2-5cos(x)+6sin^2x=0 | | 2(X+X-7)=3(X+9+X+2+X-7) | | 5x+8x-20=0 | | -2+0.9+0.5(-2)=-2.1 | | (X)(-x)(-2x)= | | 3X^2-XY=0 | | (X)(2x)(y)= | | (5x)(2x)(x)= | | 6-2x=2(1x+3) | | X=5s | | 2(7-x)+5(x+1)=10(1+x)-9(x+1) | | 400=49.91x | | 9(2x+3)=18x+27 | | 5.70=0.05x+1.70 | | 14x+43-25x=229 | | y=0.05(27)+1.70 | | 5x+8x+3x-4y= | | .25x+.5(71-x)=22 | | 8-4x=2(2x+4) | | 94-4p-6p=-1 | | 5x=100y | | 2x+(x-56)=3x | | 9r-28=-3+4r | | X-9=4x+6 | | 7r-11=-23+9t | | -2x^2+13=-43 | | 3x+3=7+7x | | 7d+40=10 | | 4x+2x+3=6x |